2017
DOI: 10.3390/ijms18020370
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy by Deguelin Sensitizes Pancreatic Cancer Cells to Doxorubicin

Abstract: Pancreatic cancer is the fourth most common cause of cancer mortality worldwide. Furthermore, patients with pancreatic cancer experience limited benefit from current chemotherapeutic approaches because of drug resistance. Therefore, an effective therapeutic strategy for patients with pancreatic cancer is urgently required. Deguelin is a natural chemopreventive drug that exerts potent antiproliferative activity in solid tumors by inducing cell death. However, the molecular mechanisms underlying this activity ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Autophagy can be induced in response to several stressors including: nutrient deprivation, chemotherapeutics, hypoxia, pathogen infection and endoplasmic reticulum stress (16)(17)(18). A larger body of research has reported that autophagy which is promoted by chemotherapeutic drugs in cancer cells, is related to drug-resistance of tumor cells (19)(20)(21). Autophagy is activated by doxorubicin in human colon cancer LoVo cells, and this autophagic activation reduces the sensitivity of cancer cells to doxorubicin (22).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy can be induced in response to several stressors including: nutrient deprivation, chemotherapeutics, hypoxia, pathogen infection and endoplasmic reticulum stress (16)(17)(18). A larger body of research has reported that autophagy which is promoted by chemotherapeutic drugs in cancer cells, is related to drug-resistance of tumor cells (19)(20)(21). Autophagy is activated by doxorubicin in human colon cancer LoVo cells, and this autophagic activation reduces the sensitivity of cancer cells to doxorubicin (22).…”
Section: Introductionmentioning
confidence: 99%
“…Gemcitabine was reported to promote autophagy in pancreatic cancer cells; treatment with gemcitabine in PANC‐1 and MiaPaCa‐2 cells resulted in upregulation of the LC3‐II and observation of autophagesomes (Mukubou, Tsujimura, Sasaki, & Ku, ). However, recent studies showed that inhibition of autophagy is also a promising approach for the treatment in pancreatic cancer (Chude & Amaravadi, ; Monma et al, ; Xu et al, ; Yang & Kimmelman, ). Chloroquine inhibits autophagy in aggressive metastatic pancreatic adenocarcinoma by inhibiting the acidification of the lysosomes in aggressive pancreatic cancer cell lines S2VP10 (Frieboes, Huang, Yin, & McNally, ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination treatment of deguelin and doxorubicin represents an effective strategy for treating pancreatic cancer . Results suggest that autophagy functions as a survival mechanism during doxorubicin treatment.…”
Section: Combination Therapy Of Deguelin With Current Cytotoxic Agentsmentioning
confidence: 99%
“…The fractions of unchanged deguelin excreted via feces and urine were approximately 1.7% and 0.4%, respectively, and this suggested that it experienced an intensive metabolism after intravenous administration. More pharmacokinetic studies in different animal models should be conducted to further evaluate pharmacokinetic parameters of deguelin such as bioavailability, which would be useful for drug development …”
Section: Pharmacokinetics and Toxicology Of Deguelinmentioning
confidence: 99%